Pengaruh Kedisiplinan, Komitmen Organisasi Dan Motivasi Terhadap Produktivitas Kerja Karyawan Pada PT Putra Gerem Jaya - Merak - Suryaman Suryaman; Nindia (Jurnal Manajemen, 2021)
ABSTRACT This study aims to determine discipline, organizational commitment and motivation to work productivity of employees at PT. Putra Gerem Jaya-Merak. This research method uses descriptive and associative quantitative methods. The data sources are primary data and secondary data. The research was conducted from December 2018 to June 2019. The study population was 63 employees of KPDC, the sample was 61 people using saturated sampling. Data were collected using research instrumens and processed using SPSS statistics version 24.00 windows. Discipline process, organizational commitment and motivation have very important roles to realizae optimal company goals requiring quality human resources, but in reality based on preliminary observations at PT. Putra Gerem Jaya-Merak work productivity is currently in a low condition because the average score has only reached 30.3, the standard score of 35, due to the accuracy of employee work with a score of 19. So it can be said that employee productivity is still not good and successful in its implementation. Based on the results of the analysis, the results obtained: discipline has no positive and insignificant effect, Meanwhile, organizational commitment and motivation have a positive and significant effect on employee work productivity either partially or jointly at PT. Putra Gerem Jaya-Merak. Keywords : Discipline, Organizational, Motivation, Employee Productivity.